Dielectric and electro-optical properties of solutions of chemically modified fullerene С60 in nematic liquid crystal - Vovk, V.E.; Kovalchuk, O.V.; Gorishnyj, M.P.; Kovalchuk, T.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
Solutions of fullerene molecules С60 with chemically attached molecules of diamine (С60D) in planar oriented nematic liquid crystal (NLC) were obtained by only heating and ultrasonic processing. The С60D concentration changes from 0 up to 3.0 wt.%. Within the ranges of frequencies 10⁻¹ – 10⁶ Hz and temperatures 298-343 K, dielectric properties of solutions were investigated. It was shown that, at frequencies higher than 100 Hz, the frequency dispersion of the components of complex dielectric permittivity is absent. A value of conductivity of the solution was determined. It was also shown that the activation energy for the temperature dependence of the conductivity in nematic and isotropic phases does not depend on the concentration of molecules С60D. Obtained and explained were the reasons of the nonmonotonic conductivity dependence of solutions on the concentration of С60D molecules. For frequencies lower than 100 Hz, the dispersion of the components of complex dielectric permittivity is observed. It was shown that the dispersion can be described by the Debye equation. The temperature dependence of a value inverse to the relaxation time correlates with the temperature dependence of conductivity. Presence of С60D molecules in NLC tends to increasing the voltage for the Frederiksz transition. Made was the assumption that this effect may be explained by increase in viscosity of NLC as a consequence of aggregation of fullerene molecules.